2013
DOI: 10.3389/fimmu.2012.00423
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C signaling and cell cycle regulation

Abstract: A link between T cell proliferation and the protein kinase C (PKC) family of serine/threonine kinases has been recognized for about 30 years. However, despite the wealth of information on PKC-mediated control of, T cell activation, understanding of the effects of PKCs on the cell cycle machinery in this cell type remains limited. Studies in other systems have revealed important cell cycle-specific effects of PKC signaling that can either positively or negatively impact proliferation. The outcome of PKC activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 207 publications
(288 reference statements)
1
92
1
1
Order By: Relevance
“…[19][20][21] Several evidences indicate PKCs as key regulators of critical cell cycle phases, including G 0 -G 1 /S transition and G 2 /M progression. [16][17][18]22 Among them, PKCα, already reported to be part of PLCβ1 signaling, 11,13,23 is known for its involvement in G 1 /S transition. 24 It has been demonstrated that, in intestinal epithelial cells, an anti-proliferative regulation of Cyclin D1 was modulated by PKCα signaling.…”
Section: Human Erythroleukemia Cells K562 Overexpressing Plcβ1mentioning
confidence: 99%
See 3 more Smart Citations
“…[19][20][21] Several evidences indicate PKCs as key regulators of critical cell cycle phases, including G 0 -G 1 /S transition and G 2 /M progression. [16][17][18]22 Among them, PKCα, already reported to be part of PLCβ1 signaling, 11,13,23 is known for its involvement in G 1 /S transition. 24 It has been demonstrated that, in intestinal epithelial cells, an anti-proliferative regulation of Cyclin D1 was modulated by PKCα signaling.…”
Section: Human Erythroleukemia Cells K562 Overexpressing Plcβ1mentioning
confidence: 99%
“…As reported in the literature, PKCs are often involved in cell proliferation targeting key proteins of cell cycle regulation, such as cyclins, cyclin-dependent kinases and cyclin inhibitors like p21/Cip1 and p27/Kip1. 16,22,[30][31][32]40,41 The most expressed PKC isoforms in K562 cells are the conventional PKCα and PKCβII and the atypical PKCζ. 42 For this reason, we screened their levels in cells overexpressing PLCβ1 to evaluate if these PKC isoforms could be affected.…”
Section: Human Erythroleukemia Cells K562 Overexpressing Plcβ1mentioning
confidence: 99%
See 2 more Smart Citations
“…However, while a variety of natural compounds activate PKCs, the outcome of PKC activation by a specific compound is highly context‐dependent, with the individual cellular targets (and off‐targets) and overall effects determined by the specific isozyme(s) involved, the timing of PKC activation, the cell type, and the signaling environment 5. This is reflected by comparing the biological activities of 12‐ O ‐tetradecanoylphorbol‐13‐acetate (TPA), bryostatin 1, and ingenol mebutate ( 2 ): the first is a strong tumor promoter, the second shows antiproliferative properties, and latter has antitumoral properties and represents the active ingredient in Picato, a marketed product for the topical treatment of actinic keratosis (solar keratosis) 6…”
mentioning
confidence: 99%